2013
DOI: 10.1016/j.ijrobp.2013.06.803
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Radiation Therapy Dose Escalation on Overall Survival in Unresectable Pancreatic Adenocarcinoma

Abstract: .Purpose: Radiation therapy (RT) dose escalation in unresectable pancreatic adenocarcinoma (PAC) remains investigational. We examined the association between total RT dose and overall survival (OS) in patients with unresectable PAC.Methods and materials: National cancer data base (NCDB) data were obtained for patients who underwent definitive chemotherapy and RT (chemo-RT) for unresectable PAC. Univariate (UV) and multivariate (MV) survival analysis were performed along with Kaplan-Meier (KM) estimates for inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
0
12
2
Order By: Relevance
“…The purpose of this analysis was to evaluate the effect of selective RT dose escalation to portions of the GTV away from bowel in patients with unresectable EHCC. Escalated dose of radiation has been shown to be associated with prolonged survival in unresectable intrahepatic cholangiocarcinoma and unresectable pancreatic ductal adenocarcinoma . Despite the acceptable toxicity of higher RT doses in our study, we found that selective escalated RT doses (up to 98 Gy BED) did not significantly benefit patients with unresectable EHCC with regard to increasing OS or FFLP.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…The purpose of this analysis was to evaluate the effect of selective RT dose escalation to portions of the GTV away from bowel in patients with unresectable EHCC. Escalated dose of radiation has been shown to be associated with prolonged survival in unresectable intrahepatic cholangiocarcinoma and unresectable pancreatic ductal adenocarcinoma . Despite the acceptable toxicity of higher RT doses in our study, we found that selective escalated RT doses (up to 98 Gy BED) did not significantly benefit patients with unresectable EHCC with regard to increasing OS or FFLP.…”
Section: Discussioncontrasting
confidence: 70%
“…Escalated dose of radiation has been shown to be associated with prolonged survival in unresectable intrahepatic cholangiocarcinoma and unresectable pancreatic ductal adenocarcinoma. [18][19][20] Despite the acceptable toxicity of higher RT doses in our study, we found that selective escalated RT doses (up to 98 Gy BED) did not significantly benefit patients with unresectable EHCC with regard to increasing OS or FFLP. Unlike intrahepatic cholangiocarcinoma, EHCC is almost always close to bowel, limiting the maximal dose and the dose coverage given to the GTV.…”
Section: Discussioncontrasting
confidence: 65%
“…While single fractions of highdose radiation (such as 10-20Gyx1) are often preferred in preclinical studies due to ease of administration (31) these subtherapeutic doses often lead to treatment failure (16) and unacceptable toxicity in both preclinical experiments and (16,32) and in clinical trials (33). Fractionated (4,34) or stereotactic (35) A common concern with radioprotectors is that they may shield tumors from cytotoxic therapy. Our data clearly demonstrate that EGLN inhibition does not increase intratumoral HIF levels ( Fig 2B) nor does it impair treatment outcomes as evidenced by the improved survival in the groups that received FG-4592.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of high-dose radiation therapy of >65Gy (high-dose) with or without radioprotection improved survival compared to all animals that received ≤65Gy (low-dose) of treatment or no RT ( Fig 3B; 37 days [95% CI [33][34][35][36][37][38][39][40][41] vs. 15 days [10][11][12][13][14][15][16][17][18][19][20][21] vs. 15 days [10-20], respectively; p=0.005). The median overall survival was compared amongst the treatment groups and was highest ( Fig 3C;…”
Section: Radiation Therapy With Egln Inhibition Improves Survival In mentioning
confidence: 99%
“…Best example maybe previously mentioned FFCD/SFRO study, where patients treated to high-dose radiation with active chemotherapy regimen resulted in inferior survival (12). Similarly, in a retrospective study based on national cancer data base, Hall et al examined radiation dose escalation above 40 Gy in CCRT but failed to validate the benefit in terms of OS (22). However, more than 54 Gy of radiation dose was associated with better OS in a more recent retrospective study by Golden et al (23).…”
Section: Discussionmentioning
confidence: 99%